An Overview on Surface Modification of Cotton Fiber for Apparel Use - Mahbubul Bashar, M.; Khan, Mubarak A. (Journal of polymers and the environment, 2013)
About 48 % cotton fiber is consumed as clothing materials all over the globe. It is popular for softness, versatility, absorbance and breathability. Cotton is hydrophilic in nature and therefore, it can absorb sweat from the human body and can release in the surface that makes it comfortable. But it has some inherent limitations such as wrinkle, shrinkage, low dye uptake and microbial degradation. Various approaches have been made to overcome the above limitations. Surface modification of textiles to impart antimicrobial activity, shrinkage, wrinkle resistance, decreased skin irritation, increase dye exhaustion and even enhancing fragrance is the most recent trends in textile chemistry. Various monomers, polymers and biopolymers are applied in different ways to improve different properties of cotton. Chitosan is the mostly used biopolymer in this regard for its biocompatibility, biodegradability, nontoxicity and antimicrobial activity. This paper is a short overview of the most recent development in surface modification of cotton using biopolymers such as chitosan, starch and its derivatives and some other synthetic monomers and polymers.